A comprehensive mechanism for the sintering of plasma-sprayed nanostructured thermal barrier coatings. Issue 13 (September 2017) - Li, Guang-Rong; Yang, Guan-Jun; Li, Cheng-Xin; Li, Chang-Jiu
Abstract: Nanostructured thermal barrier coatings (TBCs) are being widely researched for their superior thermal barrier effect and strain compliance. However, the sintering occurs inevitably in nanostructured TBCs that comprise both nanozones and lamellar zones, although the mechanism of sintering in such bimodal coatings is not yet clear. This study investigates the changes in microstructure and properties of nanostructured TBCs during thermal exposure with the aim to reveal the sintering mechanism operative in these coatings. Results show that the sintering process occurs in two stages. It was found that in the initial shorter stage (~0–10 h), the properties increased rapidly; moreover, this change was anisotropic. The main structural change was the significant healing of the intersplat pores through multiconnection. During the subsequent longer stage, the change in the properties was much smaller, where it was observed that the pores continued to heal, albeit at a much lower rate. Furthermore, the faster densification of the nanozones induced during sintering became significant, resulting in an opening at the interface between the nanozones and the lamellar zones. In brief, the pore healing at the lamellar zones affects the properties, especially in the initial stage. The presence of nanozones has a positive effect in that the performance degradation during the overall thermal exposure is slowed down. An understanding of this competing sintering mechanism would enable the structural tailoring of nanostructured TBCs in order to increase their thermal insulation and thermal cycling lifetime.